Leishmania-Host Interactions—An Epigenetic Paradigm - Afrin, Farhat; Khan, Inbesat; Hemeg, Hassan A. (Frontiers in Immunology, 2019)
Leishmaniasis is one of the major neglected tropical diseases, for which no vaccines exist. Chemotherapy is hampered by limited efficacy coupled with development of resistance and other side effects. Leishmania parasites elude the host defensive mechanisms by modulating their surface proteins as well as dampening the host’s immune responses. The parasites use the conventional RNA polymerases peculiarly under different environmental cues or pressures such as the host’s milieu or the drugs. The mechanisms that restructure post-translational modifications are poorly understood but altered epigenetic histone modifications are believed to be instrumental in influencing the chromatin remodeling in the parasite. Interestingly, the parasite also modulates gene expression of the hosts, thereby hijacking or dampening the host immune response. Epigenetic factor such as DNA methylation of cytosine residues has been incriminated in silencing of macrophage-specific genes responsible for defense against these parasites. Although there is dearth of information regarding the epigenetic alterations-mediated pathogenesis in these parasites and the host, the unique epigenetic marks may represent targets for potential anti-leishmanial drug candidates. This review circumscribes the epigenetic changes during Leishmania infection, and the epigenetic modifications they enforce upon the host cells to ensure a safe haven. The noncoding micro RNAs as post-transcriptional regulators and correlates of wound healing and toll-like receptor signaling, as well as prognostic biomarkers of therapeutic failure and healing time are also explored. Finally, we highlight the recent advances on how the epigenetic perturbations may impact leishmaniasis vaccine development as biomarkers of safety and immunogenicity.